The gap between scientific evidence and clinical practice: 5‐aminosalicylates are frequently used for the treatment of Crohn's disease. Issue 8 (22nd August 2014) - Schoepfer, A. M.; Bortolotti, M.; Pittet, V.; Mottet, C.; Gonvers, J.‐J.; Reich, O.; Fournier, N.; Vader, J.‐P.; Burnand, B.; Michetti, P.; Froehlich, F.
Summary Background There is uncertain evidence of effectiveness of 5‐aminosalicylates (5‐ASA) to induce and maintain response and remission of active Crohn's disease (CD), and weak evidence to support their use in post‐operative CD. Aim To assess the frequency and determinants of 5‐ASA use in CD patients and to evaluate the physicians' perception of clinical response and side effects to 5‐ASA. Methods Data from the Swiss Inflammatory Bowel Disease Cohort, which collects data since 2006 on a large sample of IBD patients, were analysed. Information from questionnaires regarding utilisation of treatments and perception of response to 5‐ASA were evaluated. Logistic regression modelling was performed to identify factors associated with 5‐ASA use. Results Of 1420 CD patients, 835 (59%) were ever treated with 5‐ASA from diagnosis to latest follow‐up. Disease duration >10 years and colonic location were both significantly associated with 5‐ASA use. 5‐ASA treatment was judged to be successful in 46% (378/825) of treatment episodes (physician global assessment). Side effects prompting stop of therapy were found in 12% (98/825) episodes in which 5‐ASA had been stopped. Conclusions 5‐Aminosalicylates were frequently prescribed in patients with Crohn's disease in the Swiss IBD cohort. This observation stands in contrast to the scientific evidence demonstrating a very limited role of 5‐ASA compounds in the treatment of Crohn's disease.